Comparison of different additive manufacturing methods using computed tomography - Shah, Paras; Racasan, Radu; Bills, Paul (Case studies in nondestructive testing and evaluation, 2016)
Additive manufacturing (AM) allows for fast fabrication of three dimensional objects with the use of considerably less resources, less energy consumption and shorter supply chain than would be the case in traditional manufacturing. AM has gained significance due to its cost effective method which boasts the ability to produce components with a previously unachievable level of geometric complexity in prototyping and end user industrial applications, such as aerospace, automotive and medical industries. However these processes currently lack reproducibility and repeatability with some ‘prints’ having a high probability of requiring rework or even scrapping due to out of specification or high porosity levels, leading to failure due to structural stresses. It is therefore imperative that robust quality systems be implemented such that the waste level of these processes can be significantly decreased. This study presents an artefact that is optimised for characterisation of form using computed tomography (CT) with representative geometric dimensioning and tolerancing features and internal channels and structures comparable to cooling channels in heat exchangers. Furthermore the optimisation of the CT acquisition conditions for this artefact are presented in light of feature dimensions and form analysis. This paper investigates the accuracy and capability of CT measurements compared with reference measurements from coordinate measuring machine (CMM), as well as focus on the evaluation of different AM methods.